2021
DOI: 10.14488/bjopm.2021.022
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review on Maturity Models for Digital Supply Chains

Abstract: Goal: Today, digital technologies have significant effects on supply chains as companies explore and exploit their opportunities. Digital supply chains promise advantages over traditional ones. A maturity model is a helpful tool to assess the current state of digitalization in supply chains and to guide companies towards implementation. The main goal of this paper is to investigate existing maturity models for digital supply chains and propose possibilities for future research.Design / Methodology / Approach: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…SEGURANÇA E PRIVACIDADE DE DADOS NA CADEIA DE SUPRIMENTOS DIGITAL Considerando a nova era industrial ou I4.0, a CS também pode obter ganhos por meio de tecnologia de ponta para agilizar os processos e melhorar relacionamentos entre as organizações a fim de gerar benefícios estratégicos para todas as partes (Frederico et al, 2020). Hellweg et al (2021) caracterizam como Cadeia de Suprimentos Digital (CSD) o conjunto de organizações que utiliza os facilitadores e tecnologias da era digital para manterse competitiva no mercado. Neste cenário, os desafios enfrentados por organizações, como confiança, performance, privacidade e segurança dos dados, devem ser estrategicamente pensados sob o ponto de vista coletivo.…”
Section: Revisão Bibliográficaunclassified
See 3 more Smart Citations
“…SEGURANÇA E PRIVACIDADE DE DADOS NA CADEIA DE SUPRIMENTOS DIGITAL Considerando a nova era industrial ou I4.0, a CS também pode obter ganhos por meio de tecnologia de ponta para agilizar os processos e melhorar relacionamentos entre as organizações a fim de gerar benefícios estratégicos para todas as partes (Frederico et al, 2020). Hellweg et al (2021) caracterizam como Cadeia de Suprimentos Digital (CSD) o conjunto de organizações que utiliza os facilitadores e tecnologias da era digital para manterse competitiva no mercado. Neste cenário, os desafios enfrentados por organizações, como confiança, performance, privacidade e segurança dos dados, devem ser estrategicamente pensados sob o ponto de vista coletivo.…”
Section: Revisão Bibliográficaunclassified
“…Dessa forma, os critérios apresentados nesta seção podem interferir no desempenho da segurança e privacidade de dados na CSD em níveis distintos, dependendo da maturidade da organização ou CSD. Para Hellweg et al (2021) e Weerabahu et al (2022), quanto maior a maturidade de uma organização, maior o uso de tecnologias disruptivas como facilitadores para atingir objetivos estratégicos. Neste sentido, Marinagi et al (2023) descrevem o BCK como opção para aumento da segurança e privacidade de dados.…”
Section: Revisão Bibliográficaunclassified
See 2 more Smart Citations
“…In one of the papers, the authors identified 28 models of maturity. Each focuses on a specific supply chain function or digital technology [44]. Whereas Queiroz et al proposed a new perspective on categorizing maturity levels [45].…”
Section: Modelsmentioning
confidence: 99%